The Role of Remittances in Household Spending in Rural Nepal - Resham Thapa-Parajuli; Tilak Kshetri; Sanjit Singh Thapa (Economies)
Foreign remittances have become a crucial component of the Nepalese economy. This study investigates the impact of remittances on household consumption patterns in rural Nepal using data from the World Bank’s Nepal Household Risk and Vulnerability (NHRV) Survey Panel, covering the period from 2016 to 2018. Employing an instrumental variable regression approach, we estimate the elasticity of remittances to various consumption categories. Our findings indicate that foreign remittances significantly affect total consumption expenditure. Disaggregated results reveal that remittances positively influence spending on food items and non-food categories such as education and healthcare, highlighting their role in enhancing nutrition and human capital development. However, remittances do not contribute to unproductive expenditures like tobacco, alcohol, or rituals. Therefore, other things remaining the same, remittance is enhancing welfare in rural Nepali households.